Lusitanian Amphorae on Western Mediterranean Shipwrecks: Fragments of Economic History - Bombico, Sónia (2016)
Shipwrecks constitute a primary source for the study of the ancient economy. In this paper, we will highlight some of those whose cargo contained amphorae of Lusitanian production. These are of the utmost importance for understanding the navigation routes and the Lusitanian fish products export routes in the western Mediterranean.